The negative impact on sleep for caregivers of children with intestinal failure on long-term parenteral nutrition - Christina Belza; Paul W. Wales; Darcy Fehlings; Wendy J. Ungar; Yaron Avitzur; Robyn Stremler (Intestinal Failure)
Objectives: Survival rates for children with intestinal failure (IF) have improved with care provided in the home by family caregivers. Our objective was to compare total nocturnal sleep time (TST-N) in caregivers of children with IF on home PN to caregivers of children with a chronic medical condition. Methods: A comparative cross-sectional study of sleep was completed. All participants completed actigraphy and subjective measures of sleep (Pittsburgh Sleep Quality Index [PSQI], Multidimensional Assessment of Fatigue (MAF), Epworth Sleepiness Scale (ESS)). Univariate analysis was completed with an alpha value of < 0.05 considered significant. Results: Thirty-eight caregivers of children with IF and 29 caregivers of children without a chronic medical condition participated. Caregivers of children with IF achieved less sleep than caregivers of children without a chronic medical condition (7.0 vs 7.7 h, p < 0.01) resulting in 45 min less sleep per night. Caregivers of children with IF also demonstrated a shorter period of uninterrupted sleep (2.9 vs 4.2 h, p < 0.01), increased wake after sleep onset (49 vs 29 min, p < 0.01), increased night awakenings (8.9 vs 6.0, p < 0.01) and increased PSQI scores (7.7 vs 4.3, p < 0.01) compared to caregivers of healthy children. Conclusion: Caregivers of children with IF demonstrated decreased nighttime sleep amounts and sleep quality compared to caregivers of children without a chronic medical condition. This sleep debt may have significant consequences for the long-term health and wellbeing of caregivers and highlights the importance of further research to determine what supports are required to decrease the long-term impact for IF caregivers.